PLANNING IMPLEMENTATION OF TIME ON REPEATING PROJECT WITH LINE OF BALANCE METHOD - Cindy A. Usyor; Henry Wardhana (CERUCUK, 2017)
Some projects have cleared units of similar or exactly the same on the field. Multi - unit project is classified as very rarely activities is in many cases arise from a general breakdown of activities into specific activities. The purpose of this research to determine the time required when using heading the Line of Balance as an alternative model of the development of housing projects in Banjarmasin in terms of implementation time. At the Permata Regency Perumnas V has a repetitive activity used Line of balance. LOB is a scheduling method that is "generally used for projects that have a repetitive activity this method is able reserves to demonstrate the utilization of resources, either in the form of labor, equipment or materials without interruption. LOB Application of the housing project. Permata Regency Perumnas V has a 118 days project completion time for 17 units and continuity of the work becomes more regular. By expanding the number of locations / units will work to accelerate the overall project completion time .Keywords : Time Line of Balance, Precious Regency